Adenomyosis in pregnancy mimicking morbidly adherent placenta - Theera Tongsong (2018)
The objective of this study was to illustrate a falsepositive diagnosis of adherent placenta due to underlying adenomyosis. A 34-year-old woman was diagnosed for placenta previa totalis with adherent placenta at 33 weeks, based on the findings of loss of clear space or distinguishing outline separating the placenta and uterine wall, presence of intraplacental lacunae and densely atypical vessels in the lesion. Caesarean hysterectomy was performed at 35 weeks. Pathological findings revealed placenta previa totalis with adenomyosis beneath the placenta at the lower segment, with no adherent placenta. In conclusion, this report underlines the importance of possible false-positive test of prenatal ultrasound and MRI findings of adherent placenta caused by underlying adenomyosis which could obliterate the outline distinguishing the placenta and myometrium and atypical vessels secondary to decidualisation and hypervascularity from pregnancy. This case may probably encourage physician to beware of false-positive test of adherent placenta due to adenomyosis. Copyright 2014 BMJ Publishing Group. All rights reserved.